Comparison of the alternative methods used in the surgical treatment of carpal tunnel syndrome [Karpal tünel sendromunun cerrahi̇ tedavi̇si̇nde uygulanan alternati̇f metodlarin karşilaştirilmasi] - (:unkn) unknown (My University, 2002)
Purpose: It has been observed that there are some disadvantages of open carpal tunnel release (CTR), though it is accepted as the gold standart in the surgical treatment of carpal tunnel syndrome (CTS). Endoscopic and mini open procedures have been reported as alternatives. We compared our results after these three methods. Patients and Methods: We operated 78 hands of 62 patients with idiopathic CTS. To fifty-one (65%) open, 19 (24%) endoscopic, and 8 (11%) mini open procedures were performed. Mean follow-up time was 25 months (8.46 months). Patients were evaluated for resolution of the symtoms in the early postoperative period (in three weeks), and the time until return to daily activities. The degree of patient satisfaction was questioned. Complication and recurrence rates of the procedures were compared. Results: The ratios of resolution of the symptoms in the early postoperative period after open, endoscopic, mini open procedures were 92%, 80%, 89% respectively. Patient satisfaction was defined as 'good' in all groups. Returning back to daily activities was three weeks after open CTR, while it was two weeks after other two procedures. Except existance of scar tenderness in %10 of the cases in open group, no other complication was observed in all groups. Recurrence rates in open and endoscopic groups were 2%, 10% respectively. No recurrence was determined after mini open procedure. Conclusion: The period of returning back to daily activites was shorter after endoscopic and mini open CTR, than open procedure. Patient satisfaction was good in all groups. Postoperative morbidity rate in open group was higher compared to other groups. Non of the complications mentioned in the literature after endoscopic CTR was observed. The explanation of the higher recurrence rate in the endoscopic group was proposed as our being in the learning curve for this procedure.
Keywords: Carpal tunnel syndrome; Surgical treatment; Transverse Carpal Ligament